Comparison of IAS/IFRS and OHADA standards in terms of taking inflation into account in financial accounting - MATOFALI , Victoire (Revue du contrôle, de la comptabilité et de l’audit, 2022)
Financial accounting is one of the indispensable management tools in an organization, its objective is to present financial statements that reflect a true and fair view of the assets, financial position and results of the entity. In times of high inflation, however, money loses its purchasing power at such a rate that comparing amounts resulting from transactions and other events that occurred at different times, even during the same accounting period, can be misleading. This can cause the figures in the financial statements to be misleading. It is therefore essential to adjust these figures to the actual economic conditions in order to preserve a true and fair view of the company's assets, financial position and results. International financial standards such as those of OHADA analyze this problem of inflation in accounting through different methods of restatement of the figures of the financial statements to make them faithful and consistent with the economic reality. In this work, we will identify the points of divergence as well as the points of convergence between OHADA and IAS/IFRS accounting standards in terms of inflation accounting.